Total lymphocyte count as a tool for timing opportunistic infection prophylaxis in resource-limited settings: a study from India - Srirangaraj, Sreenivasan; Venkatesha, Dasegowda (The Journal of Infection in Developing Countries, 2010)
Introduction: In resource-limited settings, due to the high cost of CD4 cell count testing, physicians must decide about opportunistic infection (OI) prophylaxis without a laboratory evaluation of HIV stage and level of immune suppression. This study aimed to evaluate the correlation of total lymphocyte count (TLC), an inexpensive laboratory parameter, to CD4 count, and to determine a range of TLC cut-offs for the initiation of OI prophylaxis that is appropriate for resource-limited settings. Methodology: Spearman correlation between CD4 count and TLC was assessed in patients attending the Anti-Retroviral Therapy (ART) centre at Mysore, India. Positive predictive value (PPV), negative predictive value (NPV), sensitivity, and specificity of various TLC cut-offs were computed for CD4 counts < 200 cells/mm3. Correlation and statistical indices were computed for all patients and for HIV patients with active tuberculosis. Results: Good correlation was noted between the 106 paired TLC and CD4 counts (r = 0.3497).TLC < 1200cells/mm3 had 88.14% sensitivity and 34.78% specificity for CD4 count < 200 cells/mm3. In those patients with active tuberculosis, TLC< 2000cells/mm3 had 95.24% sensitivity and 100% specificity for CD4 count < 200cells/ mm3. Conclusions: TLC could serve as a low-cost tool for determining when to initiate prophylaxis in resource-constrained settings.